Phytochemical Analysis, Total Phenolic, Flavonoid Contents, and Anticancer Evaluations of Solvent Extracts and Saponins of H. digitata. (4th October 2022) - Alshehri, Osama M.; Alshamrani, Saleh; Mahnashi, Mater H.; Alshahrani, Mohammed Merae; Khan, Jalwa Ali; Shah, Muhammad; Alshehri, Mohammed Ali; Zafar, Rehman; Zahoor, Muhammad; Jan, Muhammad Saeed; Hassan, Syed Shams ul; Sadiq, Abdul
Abstract : Cancer is one of the most challenging diseases in the modern era for the researchers and investigators. Extensive research worldwide is underway to find novel therapeutics for prevention and treatment of diseases. The extracted natural sources have shown to be one of the best and effective treatments for cell proliferation and angiogenesis. Different approaches including disc potato model, brine shrimp, and chorioallantoic membrane (CAM) assay were adopted to analyze the anticancer effects. Habenaria digitata was also evaluated for MTT activity against NIH/3T3 cell line. The dexamethasone, etoposide, and vincristine sulfate were used as a positive control in these assays. All of the extracts including crude extracts (Hd.Cr), saponin (Hd.Sp), n-hexane (Hd.Hx), chloroform (Hd.Chf), ethyl acetate (Hd.EA), and aqueous fraction (Hd.Aq) were shown excellent results by using various assays. For example, saponin and chloroform have displayed decent antitumor and angiogenic activity by using potato tumor assay. The saponin fraction and chloroform were shown to be the most efficient in potato tumor experiment, demonstrating 87.5 and 93.7% tumor suppression at concentration of 1000  μ g/ml, respectively, with IC50 values of 25.5 and 18.3  μ g/ml. Additionally, the two samples, chloroform and saponins, outperformed the rest of the test samples in terms of antiangiogenic activity, with IC50 28.63  μ g/ml and 16.20  μ g/ml, respectively. In characterizing all solvent fractions, the chloroform (Hd.Chf) and saponin (Hd.Sp) appeared to display good effectiveness against tumor and angiogenesis but very minimal activity against A. tumefaciens . The Hd.Chf and Hd.Sp have been prospective candidates in the isolation of natural products with antineoplastic properties.